2011
DOI: 10.4314/pamj.v9i1.71199
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of respiratory diseases seen among adults in an emergency room in a resource-poor nation health facility

Abstract: IntroductionThere is a paucity of information on utilisation of emergency medical services in Nigeria. This study was conducted to determine the pattern of respiratory diseases seen among adults in an emergency room(ER) and their mortality within twenty- four hours in a health facility in Nigeria.MethodsWe carried out a retrospective study on adult patients that presented with respiratory condition from November 2004 to December 2010 at the emergency room of Federal Medical Centre Ido-Ekiti, south western, Nig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 6 publications
3
18
2
1
Order By: Relevance
“…Our study found that 10.4% of medical emergencies were of respiratory origins. This is similar to a prevalence of 10.2% as recorded in another study done in same geographic location (7).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our study found that 10.4% of medical emergencies were of respiratory origins. This is similar to a prevalence of 10.2% as recorded in another study done in same geographic location (7).…”
Section: Discussionsupporting
confidence: 91%
“…4 ±1 6 . 5 y ear s w ith a s lig h t f emale predominance which is comparable to "a M:F ratio of 1:1.2" which was however in contrast to the sex distribution of other studies which found a slight male predominance (7,9,10). The reason for this may be as a result of improving health seeking behavior of females in our locality.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…This observation may be ascribed to physicians’ poor knowledge of smoking as risk factors for severe asthma and its blunting of the anti-inflammatory action of CSs 2627. Other factor responsible for poor recording of smoking is the perception by doctors that the most women do not smoke and is not a cause of serious morbidity among women who are mostly affected by asthma 5161728…”
Section: Discussionmentioning
confidence: 99%
“…Asthma causes an estimated 250,000 deaths annually (1 in 250 deaths worldwide) 2. Asthma is also the second leading cause of respiratory disease-related morbidity and third leading cause of respiratory disease-related emergency room visit and mortality within 24 h of admission in Ekiti State, Southwestern Nigeria 56. Smith et al .…”
Section: Introductionmentioning
confidence: 99%